Royal Ballet books Book review - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 1998)
Royal Ballet books reviews.
A House Divided. Mary Allen, Simon & Schuster, 1998. Dancing Away. Deborah Bull, Methuen, 1998. Life in Dance. Darcey Bussell, Century, 1998.